Redundant Neurovascular Imaging: Who Is to Blame and What Is the Value? - Beheshtian, E.; Emamzadehfard, S.; Sahraian, S.; Jalilianhasanpour, R.; Yousem, D.M. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Excessive use of neurovascular imaging studies such as Doppler ultrasound, CTA, MRA, and DSA adds cost to the evaluation of patients with new neurologic deficits. We sought to determine to what extent redundant neurovascular imaging is generated by radiologists’ recommendations and the agreement rates among modalities in this setting.MATERIALS AND METHODS: The radiology reports of 300 consecutive patients admitted for acute stroke to determine the frequency of the following: 1) >1 neurovascular study performed, 2) recommendation for another study, 3) recommendation made by the radiologist, and 4) agreement rates among these redundant neurovascular imaging studies.RESULTS: Among the 300 consecutive patients, 125 had redundant neurovascular imaging, accounting for 144 redundant studies. These included 75/125 redundant neurovascular imaging studies after MRA, 48/125 after CTA, and 2/125 after Doppler ultrasound. The radiologist recommended another vascular study in 22/125 (17.6%) patients; the rest of the recommendations were made by clinicians. The second study agreed with the first in 54.6% (12/22) of cases recommended by radiologists and 73.8% (76/103) recommended by clinicians (P value = .06). CTA agreed with MRA, carotid Doppler ultrasound, and DSA in 66.7%, 66.7%, and 55.6%, respectively. MRA agreed with Doppler ultrasound and DSA in 78.3% and 66.7%, respectively.CONCLUSIONS: Of cases with redundant neurovascular imaging, most were generated by clinicians, but radiologists recommended redundant neurovascular imaging in 17.6% of patients; 81.8% occurred following MRA. Overall, most secondary studies (68.8%) confirmed the findings of the first study. Such low-value, same-result redundant neurovascular imaging was more common when clinicians ordered the studies (73.8%) than when radiologists ordered them (54.6%).DUSDoppler ultrasoundRNIredundant neurovascular imaging